Power relation and knowledge: linking Islamic education to socio-political reform in Saudi Arabia - Latifah, Ainiyatul; Solihat, Ade (ATTARBIYAH: Journal of Islamic Culture and Education, 2024)
Saudi Vision 2030, conveived by His Royal Highness Prince Muhammad bin Salman (MBS), represents a transformative initiative to foster openness and shift away from Wahhabism to establish a more moderate Islam. As part of this vision, the reform of the Islamic education curriculum plays a crucial role. This study examines the curriculum reform processes and strategies, focusing on Dirasat Islamiyah textbooks addressing inter-religious and intrareligious relations. Employing a qualitative approach and text analysis, the research applies Michel Foucault's theory of power-knowledge relations to analyze the state's role in shaping educational content. The findings reveal that the reformed curriculum seeks to construct and internalize ideologies that align the younger Saudi generation with the moderate Islam agenda of MBS's government, supporting Saudi Vision 2030. This study contributes to the theoretical discourse on power-knowledge dynamics by showcasing education's role in advancing state-driven ideological shifts during significant socio-political reforms.